Using community-based methods to create a geospatial asset map of physical activity spaces in Pasadena, TX. Issue 6 (17th July 2019) - Stasi, Selina; Spengler, John Otto; Maddock, Jay; Mckyer, Lisako; Clark, Heather
Abstract : Community partners aid the development of a geospatial asset map to identify suitable placement of new physical activity spaces, amenities, and programming. Abstract: Sharing of physical activity spaces is supported by the American Heart Association and other leading public health authorities as one strategy to increase access to physical activity. The purpose of this study was to identify facilities within Pasadena, TX, that currently provide opportunities for active recreation, sport, and other forms of physical activity and analyze community access to these spaces from a geospatial perspective. Geospatial analysis was used to identify physical activity spaces and issues relevant to access. Using a community-based approach, the research team worked with partners to create a list of individuals responsible for each of the physical activity spaces. These "facility administrators" were contacted by email and then phone for a total of four attempts. Respondents were asked to complete an online shared use survey. An asset map was created from both local geospatial data (Pasadena, TX) and data from a facility access and shared use survey. Of the 39 facility administrators, 23 responded to the survey and consisted of the park director, school principals, lead pastors and clergy, and business owners. A total of 53 facilities were identified within the priority zip codes, including 30 parks, 25 schools, 9 faith-based organizations, and 4 others (a business, a nonprofit health care center, and two community-based organizations). Overall, there were 131 total amenities, and playgrounds, outdoor basketball courts, and ball fields were the most common types. Some facilities had multiple amenities at their location, including many of the parks and schools. Additionally, respondents noted other types of amenities where activity took place such as parking lots, grassy areas, classrooms, and other indoor areas. Many of the amenities, 102, were open to the general public and 28 were found to be in good condition. Findings suggest that there is inadequate access to physical activity spaces in this underserved community. There is a need for additional play spaces in Northern Pasadena and for future research bridging community health and geospatial mapping.